2018
DOI: 10.2478/pcssr-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Intelligence on OCB and EB, with Effect on Social Capital as a Mediating Variable, in a Sport Organization in Iran

Abstract: This study aimed to measure the effect of social intelligence on organizational citizenship behavior and entrepreneurial behaviors among staff members in a sport organization in Iran, with the effect on social capital as a mediating variable. The method of this study was survey, and 205 staff members were selected using stratified random sampling. The instrument in this study included four standard questionnaires measuring social intelligence (Silvera, Martinussen & Dahl, 2001), social capital (Nahapiet &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…This result implies that there is a significant relationship between social information processing and measures of organization citizenship behaviour (altruism, sportsmanship, civic virtue, conscientiousness and courtesy). The result of this study is consistent with the study of Mirsafian (2018), where an increase in staffs' social intelligence in sport organizations in Iran led to improving the staffs' extra role behaviors as well as entrepreneurial behaviors in the organization. The outcome of the study conducted by Animasahuni and Aremu (2017), revealed that social intelligence has a significant relationship with organization citizenship behviour.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result implies that there is a significant relationship between social information processing and measures of organization citizenship behaviour (altruism, sportsmanship, civic virtue, conscientiousness and courtesy). The result of this study is consistent with the study of Mirsafian (2018), where an increase in staffs' social intelligence in sport organizations in Iran led to improving the staffs' extra role behaviors as well as entrepreneurial behaviors in the organization. The outcome of the study conducted by Animasahuni and Aremu (2017), revealed that social intelligence has a significant relationship with organization citizenship behviour.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the research findings, the study concluded that organizational intelligence and its dimensions has a significant impact on organization citizenship behaviour at the physical education offices in Kermanshah province, Iran. Mirsafian (2018) aimed at measuring the effect of social intelligence on organizational citizenship behavior and entrepreneurial behaviors among staff members in a sport organization in Iran, with the effect on social capital as a mediating variable. 205 staff members were selected using stratified random sampling.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations